2016
DOI: 10.1002/ppul.23386
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich water ameliorates bronchopulmonary dysplasia (BPD) in newborn rats

Abstract: Bronchopulmonary dysplasia (BPD) is characterized by developmental arrest of the alveolar tissue. Oxidative stress is causally associated with development of BPD. The effects of hydrogen have been reported in a wide range of disease models and human diseases especially caused by oxidative stress. We made a rat model of BPD by injecting lipopolysaccharide (LPS) into the amniotic fluid at E16.5. The mother started drinking hydrogen-rich water from E9.5 and also while feeding milk. Hydrogen normalized LPS-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Studies have also shown that H 2 improves lung injuries induced by many other factors, such as hyperoxia [ 163 , 164 ], lipopolysaccharides [ 14 , 17 ], smoke inhalation [ 165 ], paraquat[ 166 ], monocrotaline [ 167 ], and extensive burns [ 168 ]. A 2013 study showed that HS pretreatment ameliorated cigarette smoking-induced airway mucus production and airway epithelium damage in rats [ 169 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%
“…Studies have also shown that H 2 improves lung injuries induced by many other factors, such as hyperoxia [ 163 , 164 ], lipopolysaccharides [ 14 , 17 ], smoke inhalation [ 165 ], paraquat[ 166 ], monocrotaline [ 167 ], and extensive burns [ 168 ]. A 2013 study showed that HS pretreatment ameliorated cigarette smoking-induced airway mucus production and airway epithelium damage in rats [ 169 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%
“…Under normal circumstances, excess ROS are neutralized in vivo by antioxidants such as glutathione peroxidase, superoxide dismutase and other antioxidant enzymes. It has been reported that lung injury may be associated with ROS [12,13]. It is known that NF-κBp65, which plays an important role in immune response, inflammatory response and apoptosis, is a transcription factor widely distributed in a variety of cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…These lung protective effects are thought to be associated with a reduction in LPS-induced p38 mitogen-activated protein kinase (p38 MAPK) and c-Jun N-terminal kinase (JNK) activation by molecular hydrogen11, 14, 15. In addition to protecting the mature lung, HRS also alleviates bronchopulmonary dysplasia (BPD) induced by LPS in neonatal mice16. Fibroblast growth factor receptor 4 (FGFR4) and vascular endothelial growth factor receptor 2 (VEGFR2) are important for maintaining alveolar structures and lung development17, 18.…”
Section: Molecular Hydrogen Against Organ Injury Induced By Sepsismentioning
confidence: 99%
“…Fibroblast growth factor receptor 4 (FGFR4) and vascular endothelial growth factor receptor 2 (VEGFR2) are important for maintaining alveolar structures and lung development17, 18. Oral intake of HRS ameliorates LPS-induced suppression of genes encoding FGFR4, VEGFR2, and heme oxygenase 1 (HO-1) in neonatal mice16. In addition, study showed19 that LPS promotes the alveolar epithelial-mesenchymal transition (EMT) and pulmonary fibrosis by increasing the production of reactive oxygen species (ROS) and transforming growth factor-β (TGF-β).…”
Section: Molecular Hydrogen Against Organ Injury Induced By Sepsismentioning
confidence: 99%